Direct cost of ambulatory care of type 2 diabetes in the middle and high income group populace of Delhi: the DEDICOM survey - Kumar, A; Nagpal, J; Bhartia, A (Journal of the Association of Physicians of India, 2008)
To estimate the direct cost of ambulatory care in diabetes patients in the middle and high income group populace of Delhi. We analyzed the drugs, investigations, consultation and monitoring related data available from a survey of 35- 65-year-old known diabetes patients conducted using a probability-proportionate-to-size 2-stage cluster design to calculate the direct cost of ambulatory diabetes care. A total of 819 subjects were enrolled from 20,666 houses. The average estimate of direct annual expenditure on ambulatory care of diabetes was approximately Rs. 6000 (approximately US$ 150). Time elapsed since diagnosis (p<0.001), education (p=0.011), gross family income (p=0.002), presence of co-morbidities (p=0.009) and requirement for useof oral hypoglycemic agents (p<0.001) or insulin (p<0.001) were significant correlates. Direct ambulatory cost of care comprised 1-3% of the gross family income of the subjects. Despite the limitations of the present study it may be concluded that a majority of the diabetes patients spend a significant proportion of their family income on diabetes related expenditure. The cost is higher for subjects with longer duration since diagnosis, those with higher education or income, those with co-morbidities and those requiring oral hypoglycemic agents or insulin.